2018
DOI: 10.1007/s40615-018-0467-0
|View full text |Cite
|
Sign up to set email alerts
|

Readmission Rates and Diagnoses Following Total Hip Replacement in Relation to Insurance Payer Status, Race and Ethnicity, and Income Status

Abstract: The present study has shown that patients on public insurance, Black patients, and patients who live in areas with lower median incomes have higher odds of readmission. Future research should focus on further identifying racial and socioeconomic disparities in readmission after THR with an eye towards implementing strategies to ameliorate these differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 51 publications
2
33
2
Order By: Relevance
“…This study, using data from strict screening and regular follow-up of CHF patients, confirms the significance of some demographic characteristics for prognosis; the results are consistent with those from other studies. [28][29][30][31] In our prediction model, anxiety showed the greatest effect on the risk of readmission, followed by paranoia, health care, independence, income, support and appetite-sleep, while the smallest contributors were gender and depression.…”
Section: Discussionmentioning
confidence: 99%
“…This study, using data from strict screening and regular follow-up of CHF patients, confirms the significance of some demographic characteristics for prognosis; the results are consistent with those from other studies. [28][29][30][31] In our prediction model, anxiety showed the greatest effect on the risk of readmission, followed by paranoia, health care, independence, income, support and appetite-sleep, while the smallest contributors were gender and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Bundled payments are a common form of value based payment 123. Several countries, including the United States, Germany, Sweden, and the Netherlands, have developed bundled payments programmes, in which healthcare organizations receive a fixed payment for services provided in discrete care episodes and are held financially accountable for spending on those episodes 456.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al 7 showed that Medicaid (as compared with private insurance) THA patients had higher odds of postoperative in-hospital mortality, increased complications, LOS and readmissions. White et al 15 showed that THA patients with Medicaid/Medicare, who are blacks, live in poorer neighborhoods and are treated at hospitals with a low surgical volume, have higher odds of readmission. Elsharydah et al found that a propensity matched cohort of black patients had higher rates of 30 day complications for lower extremity arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…6 Evidence supports the association between THA outcomes and multifactorial patient-level, provider-level and hospital-level racial and socioeconomic disparities. [7][8][9][10][11][12][13][14][15][16] Hospital safety net burden is defined as the proportion of cases at an individual hospital with the primary insurance payer being Medicaid or uninsured; safety net hospitals operate with a mandate or adopted mission to deliver care to patients regardless of their ability to pay. 17 18 Research shows higher rates of mortality, hospitalacquired infection, perioperative complications and poorer markers of surgical quality (timeliness, patient centeredness and equity of treatment) at high safety net burden hospitals.…”
Section: Introductionmentioning
confidence: 99%